Madrasah According to SKB 3 Ministers - Muhammad Rum Sitorus; Abd Mukti; Sapri Sapri (Edumaspul: Jurnal Pendidikan, 2024)
The word madrasah is synonymous with the level of formal education in the religious sphere in Indonesia, regardless of whether it is under the auspices of the government (State) or under the auspices of a foundation (Private). The aim of this research is to see the background to the birth of the 3 ministerial SKB, the objectives of the 3 ministerial SKB, the civil effect on diplomas, and the weight of religious and general subjects in the madrasah. This type of research is library research (library research using a qualitative approach. The conclusions in this research are: (1) The Minister of Education and Culture (Mendikbud), outlined three important things that were taken into consideration in preparing the SKB for the three Ministers. First, that schools have a role important and responsible in maintaining the existence of ideology and basic national consensus. Second, schools function to build insight, attitudes and character of students, educators and educational staff to maintain national unity and unity. Third, uniforms and attributes for students. educators, and educational staff at primary and secondary education levels in schools organized by regional governments (2) with the implementation of the three Ministerial Decrees, it means a) The existence of madrasas as Islamic educational institutions is more stable and stronger; b) General knowledge in madrasas is increasing; c) Physical facilities and equipment are more refined; d) There is a civil effect on madrasa diplomas. The physical facilities and improvements in madrasa equipment are an illustration that the New Order government played a very important role in the development and progress of madrasas. (3) In 1976, the decision to implement the Madrasah Curriculum was issued by the Minister of Religion, said to be a follow-up to the SKB 3 Ministers the previous year. The contents of this policy: 1. Religious subjects in madrasas 30% 2. General subjects 70% without reduction. Meanwhile, Madrasah Aliyah elective program A1 (Religious Sciences) does not apply this curriculum, because religious and general subjects have balanced percentages, namely: 47% general and 53% religion (semesters I and II); 55% general and 45% religious (semesters III and IV); 65% general and 35% religious (semester V), and 60% general and 40% religious (semester VI)